2014
DOI: 10.1186/1471-244x-14-70
|View full text |Cite
|
Sign up to set email alerts
|

The associations between ADHD and asthma in Korean children

Abstract: BackgroundThe aim of this study was to investigate the associations between attention deficit hyperactivity disorder (ADHD), the most common neuropsychiatric disorder in school children, and childhood allergic disease by evaluating their respective prevalence.MethodsSubjects were comprised of first and second grade students in twenty two elementary schools in a city in the Republic of Korea. The mode of measurement for ADHD was based on DSM-IV from clinical interviews conducted by child psychiatrists. Along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 25 publications
6
44
0
Order By: Relevance
“…Previous large epidemiological studies have shown a cross‐sectional association between asthma and ADHD in contrast to studies with small sample sizes ( N ~ 1000) . Recent analyses from nationwide population‐based studies with diagnosis based on parental report , register‐based diagnoses or prescription data reported similar ORs for the association between asthma and ADHD as we found in our study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous large epidemiological studies have shown a cross‐sectional association between asthma and ADHD in contrast to studies with small sample sizes ( N ~ 1000) . Recent analyses from nationwide population‐based studies with diagnosis based on parental report , register‐based diagnoses or prescription data reported similar ORs for the association between asthma and ADHD as we found in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Asthma and attention‐deficit/hyperactivity disorder (ADHD) are prevalent chronic health conditions in childhood, which may cause functional impairment and stress in families . There is evidence from some cross‐sectional studies to suggest an association between asthma and ADHD , while other studies did not find a relationship . Several aspects of this relationship are still poorly understood .…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the selection of participants, four studies were at unclear risk of bias [33, 34, 36, 37] whereas one study was at low risk of bias [35]. As for potential bias due to confounding, all studies were judged to have a low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Allergic diseases, such as atopic eczema (AE), AR and allergic asthma, are common childhood chronic illnesses that are estimated to affect 7 to 40% of children worldwide (28). With the deterioration of the environment due to pollution, the morbidity of allergic diseases has increased over time (29)(30)(31).…”
Section: Potential Relationship Between Adhd and Allergic Diseasementioning
confidence: 99%